Rejection of oil emulsion using tubular surface filters - Muhammad Abbas Ahmad Zaini; Iain W. Cumming; Richard G. Holdich (Universiti Kebangsaan Malaysia, 2013)
This study was aimed to characterize the rejection of oil emulsion by two tubular surface filters, namely 13 μm slots and 4 μm circular pores. A 17 mm helix was incorporated inside the filters to increase the wall shear stress. Rejection of oil, throughputs and flux decay were measured at varying shear stresses (Rw) and transmembrane pressures (TMP). The results showed that the13 μm slots produced a fairly good oil rejection of 22 μm at Rw=0.26 Pa and TMP=6.9 kPa, while the circular pores gave the rejection of 14.4 μm at Rw=0.21 Pa and TMP=34.5 kPa. The results suggested that the circular pores filter could achieve a better oil retention under lower TMP, while the slots filter could be satisfactorily operated under moderate shear stress and low TMP. The increase of TMP offered poor oil rejection by both filters and this was also true for slots-helix configuration.